COMMUNITY POLICING AS A PANACEA FOR MITIGATING ARMED BANDITARY IN CENTRAL NIGERIA - Fidelis Achoba; Peace Oluwatoyin Irefin (International Studies Journal)
Given the dearth of studies on community policing in Nigeria and Kogi State in particular, this study has focused on Ankpa Local Government Area, located in the north-east of Igalaland in Central Nigeria. The strategic location of Ankpa makes the area a cross current town between northern and southern Nigeria. Although studies on community policing in the area are equally rare, with the current global security challenges, a lot of lessons can be drawn from Ankpa’s present community policing architecture comprising the neigbourhood watch, the village committee level headed by the king and council of chiefs as well as all the other local government organised levels. Historically, community policing is as old as evolution of communities in which some of these developments have metamorphosed into urban centres. Consequent upon the creation of a modern policing system as well as other security agencies, the old community guard system drastically declined. However, as time went by, the modern policing method has not been able to curb the ever growing crime wave in the modern 774 local government areas in Nigeria. It is against this backdrop therefore that the need for community policing has become more imperative to tackle the menace of modern crimes such as banditry and terrorism. Thus, the data for this study was generated and interpreted through in depth interview with successive local government chairmen, local policemen, chiefs, elders and youths of Ankpa communities, with related literature critically reviewed.  Findings from this study reveal that the locals should be empowered for enhanced effective and efficient community policing structure as the success of food security can only be guaranteed by security of lives and property. In the final analysis, community policing will enable communities to quickly identify criminals and, through its strategic observation, alert the local police and the Nigeria Police through technology driven devices. Arising from research findings, conclusion and recommendations were made.